Slovenija in Češka v preddverju Evropske unije - Černoša, Stanislav (Teorija in praksa, 2000)
Slovenia and the Czech Republic have passed through numerous changes after attainment of independence. Transition from the economic connection with former socialist countries to the connection with Western European countries was essentially different in Slovenia than in the Czech Republic. Therefore, in the period from 1993 to 1997 the Slovene foreign trade flow of commodities was substantially more stable than the Czech foreign trade flow. In spite of that Slovenia and the Czech Republic have numerous similarities connected with the production structure or economic connection with the European Union respectively. In 90s both countries have thus similar structure of exports and imports, similar shares of intra-industry trade (GL indexes), and they also reveal similar comparative advantage (RCA indexes).
Keywords: Czech Republic; Češka; Slovenia; Slovenija; European Union; Evropska unija; države kandidatke; mednarodno sodelovanje; zunanja politika; zunanja trgovina; ekonomsko sodelovanje